PENYELESAIAN KREDIT MACET MELALUI AGUNAN YANG DIAMBIL ALIH (AYDA) PADA P.T. BANK PEMBANGUNAN DAERAH SUMATERA BARAT KANTOR CABANG JAKARTA (STUDI KASUS KREDIT MACET PT. X) - , Santya Dewi, S.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to find out the conformity between resolution of non performing loan through taken over collateral with Indonesia security law and legal consequences when at determined time limit was over the collateral foreclosed by creditor (P.T. Bank Pembangunan Daerah Sumatera Barat, Jakarta branch) is not sold. This research is empirical juridical, applies library research through taking the secondary data from law materials relating to this research. Also field research through collecting the primary data as information directly found in the research location. Taking sample uses sampling non-randomly technique with respondent selected by purposive sampling. The collected data whether from field research or library research analyzed qualitatively. Resolution of non performing loan through AYDA carried out has appropriated to UUHT especially clause 20 (2) of UUHT because there is any agreement from debtor formerly to sell the collateral under hand clause 12 of UUHT because there is not engaged in APHT or credit agreement. Regulation in banking sector doesnât explain any law effect received by bank when it doesnât complete AYDA in 1 (one) year period. The effect will appear for bank are in from of lowering bank health level, lowering profitability, bank financial liquidity and cause bad assessment from Indonesian Bank as supervisor and developer of the bank. Indonesian Bank regulation only determines that bank will get administrative sanction when it doesnât implement the resolving attempts toward AYDA.